2018
DOI: 10.1109/tuffc.2018.2794219
|View full text |Cite
|
Sign up to set email alerts
|

Multiline Transmit Beamforming Combined With Adaptive Apodization

Abstract: Increased frame rate is of high importance to cardiac diagnostic imaging as it enables examination of fast events during the cardiac cycle and improved quantitative analysis, such as speckle tracking. Multiline transmission (MLT) is one of the methods proposed for this purpose. In contrast to the single-line transmission (SLT), where one focused beam is sent in each direction, MLT beams are simultaneously transmitted and focused in several ( ) directions improving the frame rate accordingly. The simultaneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Also, for 256-element layouts the SNR is expected to drop down by 18dB, while for PA+PB the reduction is expected to be 9dB [45]. In general, limited CR and resolution can be improved by employing advanced imaging techniques such as: image coherent compounding, which, even if it limits the frame rate, has already been shown to be effective for cardiac applications based on the transmission of diverging waves [20], [21], [48]; coherence based beamforming methods in reception, enabling both improved spatial resolution and contrast [49]- [52]; adaptive and minimum variance beamformers for artifacts rejection [53]- [56]; the transmission of coded signals for the suppression of cross-talk artifacts in multiline transmission imaging [57], [58]. Also, we showed that mixed array configurations, compared to single array configurations, have a positive impact on CR; nevertheless, a further improvement could be achieved by optimizing the selection of active elements to be assigned to the transmitting and to the receiving arrays [46], [47], [59].…”
Section: Discussionmentioning
confidence: 99%
“…Also, for 256-element layouts the SNR is expected to drop down by 18dB, while for PA+PB the reduction is expected to be 9dB [45]. In general, limited CR and resolution can be improved by employing advanced imaging techniques such as: image coherent compounding, which, even if it limits the frame rate, has already been shown to be effective for cardiac applications based on the transmission of diverging waves [20], [21], [48]; coherence based beamforming methods in reception, enabling both improved spatial resolution and contrast [49]- [52]; adaptive and minimum variance beamformers for artifacts rejection [53]- [56]; the transmission of coded signals for the suppression of cross-talk artifacts in multiline transmission imaging [57], [58]. Also, we showed that mixed array configurations, compared to single array configurations, have a positive impact on CR; nevertheless, a further improvement could be achieved by optimizing the selection of active elements to be assigned to the transmitting and to the receiving arrays [46], [47], [59].…”
Section: Discussionmentioning
confidence: 99%
“…On this probe, two types of orthogonal coded excitations, i.e., one set of orthogonal Golay codes and one set of orthogonal linear frequency (FM) modulated chirps were tested since they have already been proposed for other purposes in ultrasound imaging [12][13][14][15][16][17][18][19] and are relatively simple to implement. In particular, the following Golay codes were used to obtain good orthogonal property without largely elongating the excitation duration: where G1 is complementary to G1c, G2 is complementary to G2c, the pair of G1 and G1c are orthogonal to the pair of G2 and G2c.…”
Section: Orthogonal Coded Excitationsmentioning
confidence: 99%
“…Indeed, MV adaptive beamforming could not obtain the same crosstalk reduction as simply using a Tukey apodization when received, though a better spatial resolution could be obtained [12]. Similar, the LCA adaptive apodization method using a modified predefined apodization bank could have slightly better crosstalk reduction while improving the contrast and spatial resolution, but artifacts remained visible when hyperechoic structures were presented (for instance the pericardium) [13]. The F-DMAS method could provide a better receive crosstalk suppression but the contrast-to-noise ratio would be degraded [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…tp://creativecommons.org/licenses/by/3.0/ HFR cardiac imaging techniques. Multiline transmission is an example of this, and considered an alternative approach to MLA [16]- [18]. In this technique, multiple focused ultrasound beams, typically 4 [11], are simultaneously transmitted to reduce the time needed to sweep the whole region of interest (ROI).…”
Section: Introductionmentioning
confidence: 99%